EFEKTIFITAS PIJAT REFLEKSI KAKI PADA AREA REPRODUKSI TERHADAP DISMENORE - Ninna Novriyana; Sri Utami; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dysmenorrhea ia an excessive pain during menstruation that occurs due to uncoordinated uterine contractions, this is caused by the increasing of prostaglandin production that released in the bloodstream. This study aims to determine the effectiveness of foot reflexology in the reproductive area of dysmenorrhea. This tudy was used Quasi Experimental Design with the design of Non-Equivalent Control Group. This research was carried out in Sentajo Raya 2 Public Middle School, Sentajo Raya District, Taluk Kuantan for 34 people with 17 people as an experimental group and 17 people as a control group with non probability sampling technique, that purposive sampling. The measuring instrument used in both groups was the observation sheet. The analysis was used univariate analysis to determine the frequency distribution and bivariate using altenative Wilcoxon and Mann-Whitney test. The result showed that the p value (0,000) < (0,05). This means showing that foot reflexology in the reproductive area is effective for reducing dysmenorrhea. Foot reflexology in the reproductive area can reduce dysmenorrhe pain intensity in non pharmacology which can be practiced independently, thus expected for students who have other members of family or local communities use this message for reducing dysmenorrhea pain intensity. Keywords : Adolescence, Dysmenorrhea, Foot Reflexology.